ARTISTIC IMAGES IN THE POEMS OF MUAYYAD TAYEB - Fakhri, Abdulsalam; Kak Amin, Hussein (Humanities Journal of University of Zakho, 2025)
This research attempts to introduce the poetic image of the contemporary Kurdish poet (Muayyad Tayeb) to the readers in terms of the use of poetic images and the types of images that he embodied in his poetry. This study consists of several sections which begins with an introduction to poetic imagery and then presents the origins, importance, and types of poetic imagery. After this, several poetic images are discussed such as, individual poetry images, composite poetry images, general poetry images, fixed images, moving images, images of sight, images of hearing, images of smell, images of taste, and images of touch. For each of these images, the theoretical aspects are presented first, then the practical aspects for each of these images were discussed. Three examples of our poet’s poetry are given. Poetry images represent the poet’s ideas. This idea can be taken from society, or from an event or an experience or a scene, the poet to express these feelings in poetry. As a painter, he needs to put this feeling into a literary form. Our chosen poet (Muayyad Tayeb) has succeeded in making poetic images into art. He has also had a broad contribution in conveying the emotions and the message, giving the recipients a poetic image of the poet’s identity, and readers looking for answers to their own feelings in the poem.